2014
DOI: 10.1371/journal.pone.0099763
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Clinicopathological Significance of Downregulated E-Cadherin Expression in Patients with Non-Small Cell Lung Cancer (NSCLC): A Meta-Analysis

Abstract: BackgroundMany studies have investigated the prognostic role of E-cadherin in patients with NSCLC; however, the result still remains inconclusive. An up-to data system review and meta-analysis was necessary to give a comprehensive evaluation of prognostic role of E-cadherin in NSCLC.MethodsEligible studies were searched in Pubmed, Embase and Web of Science databases. The inclusion criteria were studies that assessed the relationship between E-cadherin expression detected by immunohistochemistry (IHC) and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 42 publications
6
41
0
Order By: Relevance
“…EMT is pointed out to be crucial in tumour invasion and metastasis [42]. E-cadherin, an EMT marker, is found to be significantly associated with lymphnode metastasis and vascular invasion in patients with NSCLC [43]. In this study, overexpression of lncRNA-SVUGP2 dramatically suppressed EMT by enhancing the level of E-cadherin but depressing the levels of N-cadherin, vimentin, and snail.…”
Section: Discussionmentioning
confidence: 54%
“…EMT is pointed out to be crucial in tumour invasion and metastasis [42]. E-cadherin, an EMT marker, is found to be significantly associated with lymphnode metastasis and vascular invasion in patients with NSCLC [43]. In this study, overexpression of lncRNA-SVUGP2 dramatically suppressed EMT by enhancing the level of E-cadherin but depressing the levels of N-cadherin, vimentin, and snail.…”
Section: Discussionmentioning
confidence: 54%
“…The present results showed that the majority of tumors had conserved expression of the epithelial markers CDH1 (92%) and CTNNB1 (92%). Previous studies on E‐Cadherin expression in NSCLC tested by immunohistochemistry report conserved protein expression ranging from 32% to 88% in tumors depending on the IHC cutoff value . Moreover, an association of E‐Cadherin loss of IHC expression and the N+ status of patients was reported in several stages I to IV NSCLC cohorts .…”
Section: Discussionmentioning
confidence: 95%
“…Aerogenous spread is a phenomenon of a tumor that metastasizes through the alveolar spaces and must be achieved through cancer cells detached from the basement membrane [25]. High association with these findings with ROS1 rearranged tumors would intrigue us to investigate E-cadherin protein expression because loss of E-cadherin, a crucial cell-cell adhesion molecule, breaks down cell-cell contact, thereby malignant cells detach from the epithelialcell layer, result in tumor motility [26]. In this study, we also performed IHC of other epithelial-mesenchymal transition (EMT) markers including vimentin, snail, ␀-catenin, and matrix metalloproteinase (MMP) protein expression.…”
Section: Discussionmentioning
confidence: 99%